Education Of Prevention And Treatment In Diabete Mellitus Feet - rusdiana (Journal of Saintech Transfer, 2020)
Diabetes Mellitus is also known as "life long disease" because the disease cannot be cured during the life span of the sufferer so that people with diabetes have a risk of complications that can increase the risk of death. Diabetic foot injury is one of the most common complications, where this complication can result in decreased quality of life. With a good level of understanding of diabetes mellitus and the complications that occur we hope to reduce the incidence of diabetes foot injuries in people with diabetes mellitus.As a community team, we conduct community services which the support is under the research grant BP-PTN USU of Year 2019PPM/KP-TALENTA USU/2019, giving education on prevention and treatment of diabetic foot ulcer in Medan Johor Public Health Centre in Sumatera Utara.We used the cross sectional study. We conducted 40 respondents in type 2 diabetes mellitus who attended to public health centre and We educated them. The education provided included how to prevent and treatment of the foot ulcer of diabetes mellitus. The care and prevention of the education we provided includes how to properly take care of the feet, the periodic of glycemic control, the balanced diet and doing diabetes gymnastics. All the respondents who got the education, 25 from 40 respondents knew and did the foot care and who knew about the foot gymnastics were only 2 respondents.